2018
DOI: 10.1002/anie.201803887
|View full text |Cite
|
Sign up to set email alerts
|

A Regio‐ and Diastereoselective Anodic Aryl–Aryl Coupling in the Biomimetic Total Synthesis of (−)‐Thebaine

Abstract: The biosynthesis of thebaine is based on the regioselective, intramolecular, oxidative coupling of (R)-reticuline. For decades, chemists have sought to mimic this coupling by using stoichiometric oxidants. However, all approaches to date have suffered from low yields or the formation of undesired regioisomers. Electrochemistry would represent a sustainable alternative in this respect but all attempts to accomplish an electrochemical synthesis of thebaine have failed so far. Herein, a regio- and diastereoselect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 79 publications
(20 reference statements)
4
68
0
Order By: Relevance
“…Early studies by the Waldvogel laboratory have demonstrated that phenols can be electro‐oxidatively coupled to produce biphenols as well as polycyclic scaffolds . A related strategy was recently employed by the Opatz and Waldvogel groups in the syntheses of (−)‐thebaine and (−)‐oxycodone . Here, regio‐ and diastereoselective intramolecular anodic coupling of laudanosine derivatives afforded the corresponding morphinandienone motifs, which were further elaborated to the desired target structures (Schemes and ).…”
Section: Anodic Oxidationmentioning
confidence: 99%
“…Early studies by the Waldvogel laboratory have demonstrated that phenols can be electro‐oxidatively coupled to produce biphenols as well as polycyclic scaffolds . A related strategy was recently employed by the Opatz and Waldvogel groups in the syntheses of (−)‐thebaine and (−)‐oxycodone . Here, regio‐ and diastereoselective intramolecular anodic coupling of laudanosine derivatives afforded the corresponding morphinandienone motifs, which were further elaborated to the desired target structures (Schemes and ).…”
Section: Anodic Oxidationmentioning
confidence: 99%
“…Later, this general route was combined with anodic C−C aryl coupling to provide a biomimetic access to the natural product (−)‐thebaine ( 137 ) and the semisynthetic opioid (−)‐oxycodone (see Scheme ) . As starting materials for these syntheses, bromides 126 and 125 were prepared from methyl gallate 123 .…”
Section: α‐Aminonitriles As Key Intermediates In Natural Product Syntmentioning
confidence: 99%
“…Additionally, gallate can be easily decarboxylated to form pyrogallol, an important platform chemical used as a reducing agent in photography and dyeing agent in cosmetics. Finally, methyl gallate can be used as starting material for the synthesis of the drug precursor thebaine [34].…”
Section: -Hydroxybenzoic Acidmentioning
confidence: 99%